It makes me sick: heterosexism, homophobia and the health of gay men and bisexual men - Dodds, Catherine; Keogh, Peter; Hickson, Ford (London: Sigma Research, 2005)
"Catherine Dodds; Peter Keogh; Ford Hickson Fonds Suzan Daniel (FSD)"